The Patients whit neurotic disorders in time of Covid19. An experience of work psicogroup of WhatsApp - Juana B. Martínez Sosa; Anays González Guerra; Giselle Carreño Martínez; Marianela Fonseca Fernández; Bárbara Caridad Calderín Quiñones; Idalmis Luisa Martínez Serrano (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: Cuba and the world have suffered in recent months a health situation as a result of the new coronavirus pandemic. Psychological science began to play a key role in the health emergency, by offering first aid and psychological support. Objective: to describe the virtual psychological help modality application results for patients with neurotic disorders and their families. Methods: quantitative-qualitative, descriptive and cross-sectional study, carried out in the period April-August 2020. 28 people who gave consent to participate and had technological resources were included: 22 patients belonging to the Cienfuegos Psychiatric Hospital and 6 relatives. It was guided by psychologists and a psychiatrist. A modality of virtual psychological help was carried out using a WhatsApp group. Results: the participants demonstrated knowledge of learned psychological and psychotherapeutic resources, as well as those provided during work time. The experience was well received and considered useful, beneficial; they rated it as an excellent modality for psychological care. They overcame negative emotional symptoms related to the pandemic and there was enrichment of resources, positive group and family interaction in confinement and skills in the management of technology. Conclusions: as a new modality of psychological help, it was a timely and necessary work experience in the health emergency, proving to be effective as a work tool for psychologists and psychiatrists in psychological care.